OCEAN LAW IN TIMES OF HEALTH EMERGENCY: DEEP SEABED MINING CONTRIBUTIONS AND ITS FEAR OF OVEREXPLOITATION - de Almeida, Laisa Branco (UI Scholars Hub, 2020)
The deep seabed has one of the most enriched biodiverse places on Earth. Scientists have found some essential biomedical breakthroughs derived from hydrothermal vents involved in treating disease outbreaks among seabed minerals. Futuristic as it may sound, new pharmaceutical discoveries pressure the International Seabed Authority (ISA) into strengthening its global rules on mining exploitation beyond areas of national jurisdiction (ABNJ). This paper presents a general evaluation of the existing legal system of deep seabed mining. It highlights that, increasingly, pharmaceutical companies are shifting to ABNJ seabed areas for exploitation, pressuring the international order for a more coherent and effective mining exploitation system for the next decade. The analysis of international legal frameworks for the Law of the Sea is notable. However, there are still substantial gaps in deep seabed mining’s global governance, expected to commence soon, as ISA rushes to approve a new international mining code. The result supports a transparent mining exploitation process in ABNJ, facilitating cooperation between sectors and between countries, fostering equitable sharing, and preserving the fragile ecosystem.